2019
DOI: 10.12678/1089-313x.23.4.150
|View full text |Cite
|
Sign up to set email alerts
|

Study of Ballet Dancers During Cou-De-Pied Derrière with Demi-Plié to Piqué Arabesque

Abstract: Dancers are highly trained athletes who are at significant risk of injury due to the repetitive nature of their movement patterns. Most ballet injuries result from overuse and occur in the lower limbs. Therefore, the behavior of the lower limbs during a basic ballet movement should be studied in order to identify and subsequently correct mechanical factors that may contribute to injuries. This study analyzed a cou-de-pied derrière with demi-plié to piqué arabesque gesture executed by 18 ballet dancers identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Our questionnaire focused only on lower extremity injuries because upper extremity injuries were relatively uncommon (4%) ( Caine et al, 2016 ). In addition, the reason why professional ballet dancers have more injuries in the hip/lumbar area may come from the dancing choreography as they often have more solos and movements with leg splitting or extreme lumbar extension with large lordosis ( Mira et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our questionnaire focused only on lower extremity injuries because upper extremity injuries were relatively uncommon (4%) ( Caine et al, 2016 ). In addition, the reason why professional ballet dancers have more injuries in the hip/lumbar area may come from the dancing choreography as they often have more solos and movements with leg splitting or extreme lumbar extension with large lordosis ( Mira et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that in female adolescent DanceSport athletes in the pain group, the loading distribution and plantar pressure on the hallux further decreased and the loading value and pressure on the metatarsal increased as the HVAp increased. Mira et al [ 24 ] reported that the function of the hallux played an important role for ballet dancers, and our results suggest that in female adolescent DanceSport athletes with plantar pain in the 1st MTP joint and increasing HVAp, the function of the 1st MTP joint may have been affected.…”
Section: Discussionmentioning
confidence: 52%
“…Low back pain was not investigated in this study. Mira et al 27 compared movement patterns between beginner and experienced dancers performing piqué arabesque and found that less experienced dancers demonstrated increased lumbar side-bending away from the gesture leg and increased anterior flexion of the torso: two compensatory patterns to generate greater leg extension height. Wilson et al 28 studied trunk and pelvic inclinations during a grand rond de jambe en l'air, a circling movement of the gesture leg from a position of devant to à la seconde to an arabesque.…”
Section: Discussionmentioning
confidence: 99%